Morphometric Analysis of Human Occipital Condyle and its Clinical Significance - Shaheen Sajid Abbas Rizvi; Sharadkumar Pralhad Sawant (GAIMS Journal of Medical Sciences)
Background: There are several approaches to operate on brainstem and craniovertebral lesions and involve a resection of occipital condyles (OC). Morphological assessment of occipital condyles, aids in determining the extent and direction of condylar drilling, helping to prevent occipito-cervical destabilization and accidental damage to the neurovascular structures related here.